Revelation-Based Educational Transformation: Exploring the Principles of the Qur'an in the Dynamics of Islamic Education - Muhammad Azkia Fahmi; Uus Muhammad Husaini; Mohamad Rohman; Reni Amalia (JIA (Jurnal Ilmu Agama), 2025)
This study aims to examine the transformative role of revelation-based education by exploring the principles of the Qur’an and their relevance to the dynamics of contemporary Islamic education. The scope of the study encompasses philosophical, normative, and practical dimensions of Qur’anic principles in shaping a holistic paradigm of Islamic education. The research employs a library research method with a content analysis approach to Qur’anic verses related to educational principles, supported by classical and modern Islamic educational literature. The findings indicate that Qur’anic principles, such as monotheism (tawhid), justice, responsibility, and the development of human potential play a significant role in promoting a more integrative, humanistic, and adaptive transformation of Islamic education in response to contemporary challenges. The novelty of this research lies in its systematic effort to link the principles of revelation with the concept of educational transformation, thereby positioning the Qur’an not only as a normative source of values but also as a dynamic foundation for formulating new directions in Islamic education.